Legal Framework on Dowry and Its Challenges in India: A Critical Appraisal - Ram Shankar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
The practice of dowry, though deeply entrenched in India's socio-cultural fabric, continues to pose significant legal and societal challenges despite legislative interventions. This paper critically appraises the legal framework governing dowry in India, primarily focusing on the Dowry Prohibition Act, 1961, and its interaction with related provisions under the Indian Penal Code (Sections 304B and 498A). It examines the effectiveness, implementation, and loopholes of existing laws in curbing dowry-related violence and harassment. The abstract evaluates how gender biases, misuse of legal provisions, and systemic inefficiencies hamper justice delivery, often leading to either underreporting or misuse. Further, it discusses the role of judiciary, law enforcement agencies, and evolving jurisprudence in shaping dowry-related legal outcomes. Through a critical lens, the paper highlights the need for a nuanced, reformative approach that balances deterrence with safeguards against false accusations. In conclusion, the study underscores the importance of legal reform, public awareness, and institutional accountability in addressing the deep-rooted issue of dowry and ensuring the protection of women's rights in India.